Mildly suppressed star formation in central regions of MaNGA Seyfert galaxies. Issue 1 (3rd October 2018) - Bing, Longji; Shi, Yong; Chen, Yanmei; Sánchez, Sebastián F; Maiolino, Roberto; Riffel, Rogério; Riffel, Rogemar A; Wylezalek, Dominika; Bizyaev, Dmitry; Pan, Kaike; Drory, Niv
ABSTRACT: Negative feedback from accretion on to supermassive black holes (SMBHs), that is to remove gas and suppress star formation in galaxies, has been widely suggested. However, for Seyfert galaxies which harbour less active, moderately accreting SMBHs in the local Universe, the feedback capability of their black hole activity is elusive. We present spatially resolved H α measurements to trace ongoing star formation in Seyfert galaxies and compare their specific star formation rate with a sample of star-forming galaxies whose global galaxy properties are controlled to be the same as the Seyferts. From the comparison, we find that the star formation rates within central kpc of Seyfert galaxies are mildly suppressed as compared to the matched normal star-forming galaxies. This suggests that the feedback of moderate SMBH accretion could, to some extent, regulate the ongoing star formation in these intermediate to late type galaxies under secular evolution.